Population-based birth cohort study on diabetes in pregnancy and infant hospitalisations in Cree, other First Nations and non-Indigenous communities in Quebec - Nathalie Auger; Lin Xiao; Jill Torrie; Nancy Gros-Louis McHugh; Zhong-Cheng Luo; Rong Huang; Justin Cheng; Jane Zhu (BMJ Open)
Objectives Diabetes in pregnancy, whether pre-gestational (chronic) or gestational (de novo hyperglycaemia), increases the risk of adverse birth outcomes. It is unclear whether gestational diabetes increases the risk of postnatal morbidity in infants. Cree First Nations in Quebec are at high risk for diabetes in pregnancy. We assessed whether pre-gestational or gestational diabetes may increase infant hospitalisation (an infant morbidity indicator) incidence, and whether this may be related to more frequent infant hospitalisations in Cree and other First Nations in Quebec.Design Population-based birth cohort study through administrative health data linkage.Setting and participants Singleton infants (≤1 year) born to mothers in Cree (n=5070), other First Nations (9910) and non-Indigenous (48 200) communities in rural Quebec.Results Both diabetes in pregnancy and infant hospitalisation rates were much higher comparing Cree (23.7% and 29.0%) and other First Nations (12.4% and 34.1%) to non-Indigenous (5.9% and 15.5%) communities. Compared with non-diabetes, pre-gestational diabetes was associated with an increased risk of any infant hospitalisation to a greater extent in Cree and other First Nations (relative risk (RR) 1.56 (95% CI 1.28 to 1.91)) than non-Indigenous (RR 1.26 (1.15 to 1.39)) communities. Pre-gestational diabetes was associated with increased risks of infant hospitalisation due to diseases of multiple systems in all communities. There were no significant associations between gestational diabetes and risks of infant hospitalisation in all communities. The population attributable risk fraction of infant hospitalisations (overall) for pre-gestational diabetes was 6.2% in Cree, 1.6% in other First Nations and 0.3% in non-Indigenous communities.Conclusions The study is the first to demonstrate that pre-gestational diabetes increases the risk of infant hospitalisation overall and due to diseases of multiple systems, but gestational diabetes does not. High prevalence of pre-gestational diabetes may partly account for the excess infant hospitalisations in Cree and other First Nations communities in Quebec.